Association of plasma amyloid-β oligomerization with theta/beta ratio in older adults - Bae, Heewon; Kang, Min Ju; Ha, Sang-Won; Jeong, Da-Eun; Lee, Kiwon; Lim, Seungui; Min, Jin-Young; Min, Kyoung-Bok (Frontiers in Aging Neuroscience, 2023)
Background: Oligomeric Aβ (OAβ) is a promising candidate marker for Alzheimer's disease (AD) diagnosis. Electroencephalography (EEG) is a potential tool for early detection of AD. Still, whether EEG power ratios , particularly the theta/alpha ratio (TAR) and theta/beta ratio (TBR), reflect Aβ burden-a primary mechanism underlying cognitive impairment and AD. This study investigated the association of TAR and TBR with amyloid burden in older adults based on MDS-OAβ levels.Methods: 529 individuals (aged ≥60 years) were recruited. All participants underwent EEG (MINDD